Economics of sustainable irrigation in smallholder agriculture: Implications for food security and climate action - Urfels, Anton; Mirzabaev, Alisher; Bricx, Stephen; Deb, Proloy; Dewi, Kumala; Evangelista, Gio; Flor, Rica Joy; Harris, Ben; Jayasiri, Nishanka; Kishore, Avinash; McDonald, Andrew J.; Mondal, Manoranjan; et al. (IOP Publishing, 2024)
Irrigation is crucial for food systems transitions, contributing to food security, climate change mitigation and adaptation, and poverty reduction (Rosa 2022, McDermid et al 2023). Similarly, population growth, economic development, and climate change exacerbate physical and economic water scarcity, requiring concerted efforts for agricultural water use to stay within sustainable boundaries (de Graaf et al 2019, Hendriks et al 2023, Mehta et al 2024). Consequently, sustainable irrigation—ie irrigation for healthy food production through fair water use within planetary boundaries—is (re) emerging as an important field of study. Sustainable irrigation aims to understand how, when, and where to bring water systems and agricultural systems in balance—ie harmonise water use for food security, economic development, and environmental sustainability. This includes estimating changing crop water requirements, water availability, earth system feedbacks, and low-emission irrigation strategies (Jain et al 2021, Vereecken et al 2022, Yuan et al 2024). However, defining context-specific goals and navigating transitions remains insufficiently considered, with inadequate attention paid to social, technological, ecological, institutional, and economic factors that often make irrigation transitions difficult to achieve in practice. Importantly, the idea of water as a human right that is freely available to all conceals the actual economic cost many farmers incur for delivering water. These can range from a few dollars up to $200+ per season. To address this, this (re) emerging field of sustainable irrigation can build on international policy recommendations for valuing water, such as the Mar del Plata conference (UN 1977), the Dublin Principles (WMO 1992), the High-Level Panel on Water (HLPW 2018), the UN Valuing Water Initiative, and the Bellagio principles (HLPW 2017). Although formerly focusing on the productive value of water, these policy initiatives now embrace a stronger focus on inclusivity, multiple water users, and ecosystem services and allow for a common platform to discuss, envision, and plan for sustainable irrigation systems. However, these previous policy and research initiatives have not yet systematically collected data on irrigation systems and water cost globally nor analysed how irrigation economics can inform policy or program design to achieve sustainability goals across regions. Here, we argue that a more substantial focus on the economics of water delivery and its human and natural drivers is required to inform sustainable irrigation discussions and move the needle on reaching global challenges such as zero hunger, poverty reduction, clean water for all, and climate action.